End-Stage Kidney Disease: A Survey of Recent Research to Support a Palliative Approach. (May 2014) - Crawford, Gregory B.; Robinson, Julie A.; Baker, Amy E. Z.; Crail, Susan M.
This survey examines the quantity, quality, and accessibility of recent research that contributes to the evidence-based implementation of a palliative approach to end-stage kidney disease (ESKD). An electronic search identified published articles (between September2009 and August 2011) relevant to adults with ESKD (n = 1628). Few articles (n = 136) referred to key themes in a palliative approach to care: life-limiting illness, holistic care, and unit of care. Most of the relevant empirical articles used designs that did not allow a causal variable to be identified, and evaluations of interventions were rare. The literature was dispersed and often in journals unlikely to be regularly accessed by renal clinicians. Literature supporting the implementation of a full evidence-based palliative approach to ESKD is expanding but remains limited and is difficult to identify and access.